Influence of dietary fiber and copper on growth performance and carcass characteristics of finishing pigs and utilizing linear programming to determine pig flow - Coble, Kyle Francis (Kansas State University, 2015)
A total of 7,061 finishing pigs were used in 7 experiments. Experiment 1 investigated the effects of withdrawing high-fiber ingredients prior to marketing to optimize growth performance, carcass yield, and carcass fat quality. Switching pigs from a high-fiber to a low-fiber corn-soy diet approximately 15 to 19 d before slaughter restored carcass yield and partially decreased carcass fat IV compared to pigs fed the high-fiber diet until slaughter. Experiment 2 studied 30% distillers dried grains with solubles (DDGS) and 5% added fat prior to slaughter on growth performance and carcass characteristics. Adding 5% fat to finishing pig diets containing 30% DDGS approximately 20 d before slaughter improved ADG and G:F but did not overcome the reduction in carcass yield from feeding DDGS. Experiment 3 investigated the Cu source on growth performance and carcass characteristics. Increasing dietary Cu in high byproduct diets improved growth and feed intake, resulting in increased final BW and HCW for pigs fed both Cu sources. Experiment 4 examined added Cu and standardized ileal digestible (SID) lysine (Lys) level on growth performance, carcass characteristics, and carcass fat quality. Feeding 150 mg/kg Cu to pigs in the 100% SID Lys requirement diet had improved growth but in the 85 or 92.5% SID Lys requirement diet no response to added Cu was found. Furthermore, increasing SID Lys increased ADG and HCW, but added Cu did not influence growth when feeding low SID Lys. Experiment 5 investigated diet ingredient type and added Cu on growth performance, carcass characteristics, gross energy digestibility, and small intestine histology and gene expression. When comparing diet type and added Cu, pigs fed a byproduct diet with DDGS and bakery meal tended to have lower G:F and reduced HCW compared to pigs fed a corn-soy diet. Adding Cu did not influence growth or carcass characteristics. However, adding Cu to the byproduct diet improved gross energy digestibility and decreased the crypt depth in the distal small intestine. Finally, a linear programming model was developed as a decision tool for commercial swine producers to help guide pig flow decisions to maximize the return to the operation.
Keywords: Finishing pigs; Copper; Growth; Linear programmingFiber; Animal Sciences (0475)